Analisis perbedaan kolerasi data AIP Text dengan data Chart pada Bandar Udara Sultan Mahmud Badaruddin II - Assaliky, Ammaida; Eka Putra, Andhika; Permatasari, Novita Ayu (Jurnal Bisnis dan Operasi Penerbangan, 2025)
Inconsistencies in AIP documents can lead to confusion for users of aeronautical information. This study examines the discrepancy in Taxiway G strength data at Sultan Mahmud Badaruddin II International Airport, Palembang, as recorded in AIP VOL II WIPP AD 2.8 Aprons, Taxiways And Check Locations/Positions Data compared to WIPP AD 2.24-1 Aerodrome Chart – ICAO and WIPP AD 2.24-2 Aircraft Parking/Docking Chart – ICAO. In WIPP AD 2.8, the strength of Taxiway G is listed as PCN 39/F/C/X/T, while in WIPP AD 2.24-1 and WIPP AD 2.24-2, it is listed as PCN 39/F/C/W/T. The study aims to identify the source of the inconsistency, evaluate its impact on the efficiency of data dissemination, and provide recommendations to improve the validity of aeronautical publications. The findings indicate that the inconsistency stems from discrepancies in data during the document compilation process. The recommendations include improving coordination procedures among personnel and adjusting Quality Control oversight to ensure data consistency. Keywords: AIP, Taxiway, PCN, information consistency, Quality Control